Performance Testing of a Venturi-Based Backpack Spray Decontamination System. (March 2020) - Beswick, Alan; Bailey, Claire; Crook, Brian; Crouch, David; Farrant, Jayne; Frost, Gillian; Stagg, Stephen
Introduction: The performance of 2 disinfectant chemicals, peracetic acid (PAA) and hypochlorous acid (HOCl), was evaluated using a Venturi-nozzle-based light decontamination system (LDS) for delivery. The atomization equipment combined low-pressure air and disinfectant via a handheld lance, producing a fine, dense aerosol. A range of microorganisms, including Bacillus cereus and Bacillus anthracis ( Vollum ) spores, were used as test challenges to evaluate chemicals and equipment. Methods: The tests undertaken included assessments over fixed and variable exposure times, use of multiple surface materials, and a live agent challenge. Results: Over a fixed-time exposure of 60 minutes, aerosolized PAA gave 7- to 8-log reductions of all test challenges, but HOCl was less effective. Material tests showed extensive kill on most surfaces using PAA (≥6-log kill), but HOCl showed more variation (4- to 6-log). Testing using B. anthracis showed measurable PAA induced spore kill inside 5 minutes and >6-log kill at 5 minutes or over. HOCl was less effective. Discussion: The results demonstrate the importance of testing decontamination systems against a range of relevant microbiological challenges. Disinfectant efficacy may vary depending on product choice, types of challenge microorganisms, and their position in a treated area. The most effective disinfectants demonstrate biocidal efficacy despite these factors. Conclusion: The data confirmed PAA as an effective disinfectant capable of rapidly killing a range of microorganisms, including spores. HOCl was less effective. The LDS system successfully delivered PAA and HOCl over a wide area and could be suitable for a range of frontline biosecurity applications.